Bioassay system for the detection of aryl hydrocarbon receptor agonists in waterborne pesticides using zebrafish cyp1a1 promoter-luciferase recombinant hepatic cells. (April 2019) - Zhou, Yixi; Shen, Chao; Du, Hong; Bao, Yuanyuan; He, Chengyong; Wang, Chonggang; Zuo, Zhenghong
Abstract: Currently used pesticides are widely distributed in surface water. Most of them are harmful to aquatic animals. In the present study, a novel recombinant hepatic cell line was developed for detecting the activity of aryl hydrocarbon receptor (AhR) agonists, and their potential bio-toxicity to aquatic animals was evaluated. First, HepG2 cells were stably transfected with a luciferase reporter plasmid containing a zebrafish ( Danio rerio ) cyp1a1 promoter with twelve copies of dioxin-responsive elements. The minimal detection limit was a 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) concentration of 0.3 ng/L (equivalent to 0.93 pM). The AhR agonist activity of thirty-seven pesticides was screened by measuring luciferase expression in the recombinant cells. Four pesticides (ipconazole, mepanipyrim, quinoxyfen and pencycuron) significantly induced luciferase expression. Additionally, cells treated with these four pesticides increased the cyp1a1 mRNA expression level, which further confirmed that they are AhR agonists. In conclusion, for the first time, we developed recombinant hepatic cells with a luciferase reporter plasmid containing a modified zebrafish cyp1a1 promoter. The cyp1a1 promoter luciferase reporter cells can be used as a sensitive and specific model to screen AhR agonists among currently used pesticides in water, which could be beneficial for risk assessment in aquatic environments. Highlights: Novel cells containing a modified zebrafish cyp1a1 promoter sensitively and specifically respond to AhR agonists. The minimal detection limit of recombinant cells is less than 0.3 ng/L TCDD. Ipconazole, mepanipyrim, quinoxyfen and pencycuron were demonstrated to possess AhR agonist activity.